Ho Chi Minh City, Vietnam: A Case Study in Mental Health Marketing - Lena Bucatariu; Babu George (TIJAB (The International Journal of Applied Business), 2020)
Following the phenomenological case study method, this paper highlights the mental health marketing scenario in Ho Chi Minh City, Vietnam. While the developed world is finding modern methods to connect with and serve MH patients, Vietnam and most other developing economies are still struggling to shift views from mental illness to mental wellness. Despite this, particularly among a small group of forward thinking providers, there is a trend taking shape towards more proactive and digitally-savvy identification, acquisition, and retention of mental health patients. In addition to de-stigmatizing mental health issues, this has the effects of providing patients access, confidence, and meaningful engagement. Marketing orientiation also resulted in increased attention to preventive mental healthcare.